Participação social e contextos de vulnerabilidade em pessoas acometidas pela hanseníase nos municípios de Vitória da Conquista e Tremedal, Bahia – 2001 a 2014 - Fernandes, Thayse Andrade (2016)
The Hansen's disease is characterized as chronic infectious disease that provokes severe disorders of peripheral nerves and causes disability and deformities that reach individuals in their ability to work and social life, mainly those who are at an economically active age group. Addressing people affected by the Hansen’s disease pervades by the completeness of the care and the social participation characterizes itself then as a fundamental element to be recognized to the attention given by the public health system. By the characteristic of neglected disease, the Hansen's disease also signals the necessity to approach both collective and individual dimensions, being viable to surpass the conduct exclusively clinical when using the perspective of vulnerability. Objective: to characterize the participation restriction and contexts of vulnerability in people afflicted by Hansen's disease in the period of 2001 to 2014, in the municipalities of Vitória da Conquista and Tremedal-Bahia. Methodology: Cross-sectional, descriptive, quantitative study linked to national project. To sort out the participation, it was used the scale of Participation v. 4.6. Clinical assessment sociodemografic tools were applied. For the data entry masks were built in Epi info 3.5.4 and the analysis made in the program STATA/SE 13.1. Results: 288 people affected by Hansen's disease were addressed in Vitória da Conquista and 46 in Tremedal. Being most female, brown colored skin, with education up to elementary school and married/stable relationship. Most with multibacillary operational classification (64.98% in Vitória da Conquista and 90.62% in Tremedal), borderline clinical form in 43.35% in Vitória da Conquista and Tremedal 40.74% both for borderline as to physical disability, Lepromatous represent 63.71% in Vitória da Conquista and 74.42% in Tremedal. The restriction to participation showed to be present in 24.49% in Vitória da Conquista and 33.33% in Tremedal. The vulnerabilities have been categorized on an analysis matrix composed of categories of individual, social and programmatic dimensions. For the context of individual vulnerability and the restriction on social participation, The degree of incapacity pointed out that 58.70% of those with level 2 had some restrictions to participation in Vitória da Conquista. The borderline clinical form represents 19.59% classified as restricted light/moderate and 15.38% with lepromatous clinical form with acute/extreme stint at Vitória da Conquista. For Tremedal, Tuberculoid clinical form represents 33.33% with mild/moderate restriction and 20.00% with mild/moderate restrictions and severe/extreme with lepromatous clinical form. For the socially vulnerable people in inactivity to work in Vitória da Conquista showed with 39% with any restrictions and Tremedal 39.39% of the people with restriction to participate live in extreme poverty. The vulnerability was expressed in standard analysis, composed of categories of individual, social and programmatic dimensions. Conclusion: The services may incorporate the use of the Scale of Social Participation in the monitoring of people affected by Hansen's disease because it is configured as a tool that is easy to apply and allows the health professional to approach issues related to the life situations of the person with leprosy and thus assist in the planning of prevention and rehabilitation actions. The risk analysis does not reach an understanding of the complexity of the vulnerability, and if you consider the relationships between variables, their contexts and dimensions by integrating people afflicted by Hansen's disease in all the possibilities of action for reducing the damage caused by the disease.